2020
DOI: 10.1111/jac.12452
|View full text |Cite
|
Sign up to set email alerts
|

Water stress and warming impact nutrient use efficiency of Mombasa grass (Megathyrsus maximus) in tropical conditions

Abstract: Temperature and other abiotic factors, such water and nutrient availability, play an important role for plants in response to the changing environments. At this regard, both warming and drought might affect the nutrient use efficiency (NUE) and growth of Megathyrsus maximus a C4 forage grass of high interest for cattle feeding. However, the nutrient requirements of this species under climate change are unknown. Therefore, we aimed to evaluate the individual and combined effects of two levels of temperature: am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 48 publications
2
17
0
4
Order By: Relevance
“…Leaf ash content increased with WW treatment. This finding is consistent with other research that reported an increase in most leaf nutrient under well‐irrigated condition (Olivera‐Viciedo et al., 2020), especially those nutrients that are passively uptaken (Wu et al., 2012). Furthermore, ash content has been positively correlated with transpiration ratio (ratio of water transpired to carbon fixed) (Masle, Farquhar & Wong, 1992; Merah, Deleens, Souyris & Monneveux, 2001), and an increase in the later can occur under well‐irrigated condition.…”
Section: Discussionsupporting
confidence: 93%
“…Leaf ash content increased with WW treatment. This finding is consistent with other research that reported an increase in most leaf nutrient under well‐irrigated condition (Olivera‐Viciedo et al., 2020), especially those nutrients that are passively uptaken (Wu et al., 2012). Furthermore, ash content has been positively correlated with transpiration ratio (ratio of water transpired to carbon fixed) (Masle, Farquhar & Wong, 1992; Merah, Deleens, Souyris & Monneveux, 2001), and an increase in the later can occur under well‐irrigated condition.…”
Section: Discussionsupporting
confidence: 93%
“…Olivera Viciedo et al. (2020) studied the impacts of water deficiency on Megathyrsus maximus and found a reduction in plant dry matter under such stress.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of plants to use absorbed nutrients to compose its tissues has a direct influence on biomass production 61 , 79 . Therefore, P deficiency in relation to P-sufficient plants reduced nutritional homeostasis and the use efficiency of C and N, affecting forage plant growth in both cycles and in the two soils studied, with a decrease in dry matter production dries of 50 and 31% in plants grown in Oxisol and Entisol, respectively.…”
Section: Discussionmentioning
confidence: 99%